Analisis Mikrobiologis Tentang Analisis Mikrobiologis dan Karaketristik Bakteri Asam Laktat Fermentatif Pada Ikan Bekasam Tradisional Melalui Pewarnaan Gram dan Uji Mikroskopis - Zaskia Rahmawati; Ardi Mustakim (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Bekasam is a traditional fermented fish product commonly produced in South Sumatra and South Kalimantan, known for its distinctive sour taste resulting from the metabolic activity of lactic acid bacteria (LAB). LAB play a crucial role in the fermentation process, contributing to the product’s flavor, texture, and safety. This study aimed to isolate, identify, and characterize LAB from bekasam made using tilapia (Oreochromis niloticus). Isolation of bacterial strains was performed using the pour plate method on Nutrient Agar (NA) medium at various serial dilutions to obtain discrete colonies. The colonies were observed macroscopically to assess their morphological characteristics, including shape, size, color, surface texture, and edge profile. Further identification involved Gram staining to determine cell wall type and microscopic morphology. The results revealed that the bacterial colonies were generally small, round, white to cream in color, with smooth surfaces and flat edges. Gram staining demonstrated that the dominant isolates were Gram-positive bacteria, exhibiting rod-shaped or oval morphology. These characteristics are consistent with members of the genus Lactobacillus sp., a common LAB group in fermented fish products. Additional phenotypic traits observed included catalase-negative reactions, absence of spore formation, and the ability to produce lactic acid as the main metabolic end product. The combination of morphological, staining, and basic biochemical characteristics supports the initial identification of the isolates as LAB. The presence of Lactobacillus sp. in bekasam suggests their significant contribution to the fermentation process, influencing the product’s sourness, safety, and preservation. The findings of this study provide a basis for further molecular characterization and potential selection of LAB strains as starter cultures to improve the quality, consistency, and safety of bekasam in traditional and industrial production.